Case-matched Comparison of Robotic Versus Laparoscopic Proctectomy for Inflammatory Bowel Disease. Issue 3 (June 2016) - Rencuzogullari, Ahmet; Gorgun, Emre; Costedio, Meagan; Aytac, Erman; Kessler, Hermann; Abbas, Maher A.; Remzi, Feza H.
Abstract : The present study reports an early institutional experience with robotic proctectomy (RP) and outcome comparison with laparoscopic proctectomy (LP) in patients with inflammatory bowel disease (IBD). Patients who underwent either RP or LP during proctocolectomy for IBD between January 2010 and June 2014 were matched (1:1) and reviewed. Twenty-one patients undergoing RP fulfilled the study criteria and were matched with an equal number of patients who had LP. Operative time was longer (304 vs. 213 min, P =0.008) and estimated blood loss was higher in the RP group (360 vs. 188 mL, P =0.002). Conversion rates (9.5% vs. 14.3%, P >0.99), time to first bowel movement(2.29±1.53 vs. 2.79±2.26, P =0.620), and hospital length stay(7.85±6.41 vs. 9.19±7.47 d, P =0.390) were similar in both groups. No difference was noted in postoperative complications, ileal pouch to anal canal anastomosis-related outcomes, Cleveland Global Quality of Life, and Short Form-12 health survey outcomes between RP and LP. Our good results with standard laparoscopy are unlikely to be improved with robotics in proctectomy cases. Potential benefits of robotic approach for completion proctectomy warrant further investigation as experience grows with robotics.